2009
DOI: 10.1128/jvi.02149-08
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of the Postmitotic Checkpoint Contributes to Polyploidization in Human Papillomavirus E7-Expressing Cells

Abstract: High-risk types of human papillomavirus (HPV) are considered the major causative agents of cervical carcinoma. The transforming ability of HPV resides in the E6 and E7 oncogenes, yet the pathway to transformation is not well understood. Cells expressing the oncogene E7 from high-risk HPVs have a high incidence of polyploidy, which has been shown to occur as an early event in cervical carcinogenesis and predisposes the cells to aneuploidy. The mechanism through which E7 contributes to polyploidy is not known. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 39 publications
4
27
0
3
Order By: Relevance
“…To test this possibility, we added nocodazole to trap cells that may have bypassed the G 2 checkpoint in mitosis. Our previous studies have demonstrated that HPV E6 and E7 do not have much effect on the spindle checkpoint and that cells expressing E7 arrest in mitosis for an extended period of time (25). As shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…To test this possibility, we added nocodazole to trap cells that may have bypassed the G 2 checkpoint in mitosis. Our previous studies have demonstrated that HPV E6 and E7 do not have much effect on the spindle checkpoint and that cells expressing E7 arrest in mitosis for an extended period of time (25). As shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Although no significant spontaneous polyploidy was seen in early-passage RPE1 cells expressing E7 (Fig. 1B), over an extended period of culture, a small but statistically significant increase in the percentage of polyploidy in these cells has been found (25). Bleomycin treatment enhanced the extent of DNA damage (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is reported that expression of either HPV E6 or E7 alone is sufficient to deregulate cytokinesis and consequently produce the tetraploid cell (Heilman et al, 2009). However, it was demonstrated that the formation of these cells is primarily attributed to E5-induced cell fusion, rather than E6, E7, and cytokinesis failure (Ho et al, 2009).…”
Section: The Role Of the E5 Proteinmentioning
confidence: 99%
“…First, either HR-HPV E6 or E7 alone can also contribute to tetraploid cell formation by inducing cytokinesis failure (Incassati et al, 2006;Heilman et al, 2009;Duensing et al, 2001a). Second, it is widely accepted that increasingly deregulated expression of E6 and E7 has been identified as the major transforming factor in the pathogenesis of cervical dysplasia and derived cancers.…”
Section: Do Those Vaccines Activate the Immune Memory System?mentioning
confidence: 99%